Synergistic removal of pharmaceuticals and antibiotic resistance from ultrafiltered WWTP effluent: Free-floating ARGs exceptionally susceptible to degradation - Gajdoš, Stanislav; Zuzáková, Jana; Pacholská, Tamara; Kužel, Vojtěch; Karpíšek, Ivan; Karmann, Christina; Šturmová, Rebecca; Bindzar, Jan; Smrčková, Štěpánka; Sýkorová, Zuzana; Srb, Martin; Šmejkalová, Pavla; et al. (Journal of environmental management, 2023)
To protect the environment and human health, antibiotic resistance genes (ARGs) and persistent pharmaceuticals need to be removed from WWTP effluent prior to its reuse. However, an efficient process for removing free-floating extracellular DNA (exDNA) in combination with a wide range of pharmaceuticals is yet to be reported for real process conditions. As a possible solution, we treated real ultrafiltered WWTP effluent with UV/H2O2 and combined GAC and zeolite sorption. In terms of exDNA, sequencing and high-throughput quantitative PCR (HT-qPCR) showed that exDNA is a potent carrier of numerous ARGs in ultrafiltered WWTP effluent (123 ARGs), including multi-drug efflux pump mexF that became the dominant exARG in GAC effluent over time. Due to the exposure to degradation agents, exDNA was reduced more efficiently than intracellular DNA, and overall levels of ARGs were substantially lowered. Moreover, GAC sorption was particularly effective in the removal of almost all the 85 detected pharmaceutical residues, with fresh GAC demonstrating an efficiency of up to 100%. However, zeolite (Si/Al 0.8) addition was needed to enhance the removal of persistent pollutants such as gabapentin and diclofenac to 57% and up to 100%, respectively. Our combined approach eminently decreases the hazardous effects of pharmaceuticals and antibiotic resistance in the ultrafiltered WWTP effluent, producing effluent suitable for multiple reuse options according to the latest legislation. In addition, we provided similarly promising but less extensive data for surface water and treated greywater.
Keywords: léčivé přípravky; Humans; antibiotická rezistence; Pharmaceutical Preparations; Genes, Bacterial; Zeolite; Municipal effluent; lidé; Zeolites; antibakteriální látky; Water reuse; Wastewater; zeolity; Anti-Bacterial Agents; peroxid vodíku; bakteriální geny; Advanced oxidation process; Extracellular antimicrobial resistance genes; Drug Resistance, Microbial; odpadní voda; Micropollutants; Hydrogen Peroxide